Hubungan Dukungan Suami Dengan Tingkat Kecemasan Menghadapi Persalinan Pada Ibu Hamil Primigravida Trimester III - Ema Maryati; Indah Sri Wahyuni; Agnomelsya Bangaran (Indonesian Journal of Midwifery Scientific, 2025)
Background: Anxiety in pregnant women can arise, especially in the third trimester of pregnancy until the time of delivery,during this period pregnant women feel anxious about various things such as normal or abnormal birth of the baby, thepain that will be felt, and so on. Objective: To determine the relationship between husband's support and the level ofanxiety facing childbirth in third trimester primigravida pregnant women in the work area of the Sukalarang HealthCenter in 2024. Methodology: This type of research is a quantitative type of research. The design used in this research isa cross sectional approach. The population in this study was all third trimester primigravida pregnant women in theSukalarang Health Center working area, totaling 88 people. The sample in this research was 88 respondents. Thesampling technique uses total sampling. This research began to be conducted in February 2024. The data collection toolused in this research was a questionnaire. Results: univariate analysis showed that primigravid pregnant women in thethird trimester received information support as many as 56 (63.6%) respondents, received assessment support as manyas 54 (61.4%) respondents, received instrumental support as many as 55 (62.5%) respondents, 53 (60.2%) respondentsreceived emotional support, and 59 (67.0%) respondents experienced moderate anxiety. Bivariate analysis showed thatthere was a relationship between husband's support (information support, assessment support, instrumental support andemotional support) with the level of anxiety facing childbirth in third trimester primigravida pregnant women in theCicurug Community Health Center working area in 2024. Conclusions and Suggestions: there is a relationship betweeninformation support, assessment support, instrumental support and emotional support with the level of anxiety facingchildbirth in third trimester primigravida pregnant women in the Cicurug Community Health Center working area in2024. It is hoped that husbands will always accompany their wives both before childbirth and during childbirth, as wellas meeting all the needs of pregnant women, providing more intense affection and exchanging information.